Using one health training for interprofessional team building: implications for research, policy, and practice in Nigeria - Shehu, Nathan; Luka, Pam; Bente, Dennis; Weka, Rebecca; Weldon, Caroline; Pam, Dung D.; Cadmus, Simeon; Dami, Filibus; Paessler, Slobodan; Weaver, Scott; Dacso, Matthew (Frontiers in Public Health, 2024)
In recent years, the concept of One Health (OH) has arisen as an approach that helps to catalyze the creation of transdisciplinary teams needed for surveillance and investigation of emerging disease dynamics. Besides a wealth of descriptions of what the OH approach encompasses, a dearth of information is available regarding the training of individuals in OH competencies. In 2019, the Nigerian Center for Disease Control developed an OH strategic plan to meet the country`s human, animal, and environmental health challenges. In response to the demand for clinicians, scientists, climatologists, conservationists, and environmentalists, who have expertise in environment, human, plant, and animal health to work collaboratively in addressing OH challenges in Nigeria. An interprofessional group of faculty from the University of Texas Medical Branch, the University of Jos, and the National Veterinary Research Institute convened to develop a novel OH course 'entitled 'One Health for Translational Team Science. The objective of the course was to explore the evolution of an emerging epidemic, capitalizing on various learning environments, including animal, environmental, human, and public health perspectives. The 6-week course comprised of three parts: 2-weeks virtual part of case-based group discussions focusing on animal and environmental aspects, two weeks of individual field experiences, and a final virtual part focusing on human health. Pedagogical tools used were: case-based group discussions, breakout group presentations, role-play activities, field project write-up, peer evaluation, group writing assignments, and weekly reflections with the goal of working in teams to develop and practice the fundamental leadership and management skills in addressing emerging public health challenges. Post-course evaluations showed that all participants felt more confident identifying and practicing the necessary attitudes and skills to participate effectively in the evaluation of an outbreak. Furthermore, the roles, responsibilities, and ''One Health ways of thinking'' for the various disciplines and professions involved in improving global health were articulated and identified.